2018
DOI: 10.31055/1851.2372.v53.n1.19913
|View full text |Cite
|
Sign up to set email alerts
|

La domesticación del paisaje en enclaves pluriculturales del sur de Misiones (Argentina): Una aproximación a través de los cítricos.

Abstract: Los cítricos son frutales introducidos tempranamente a América. Actualmente para Misiones se reconocen 30 etnovariedades (9 etnoespecies), cultivadas de maneras diversas. En la presente contribución se describen los microambientes donde se encuentran, las prácticas sobre dichos microambientes y las etnovariedades presentes en cada uno para luego analizar, desde un enfoque relacional, el efecto de las prácticas de manejo en los procesos de domesticación de las plantas y del paisaje. Los trabajos de campo fueron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Likewise, when analyzing the way these landscape units are named, a complex series of factors is involved. Most of the names assigned describe biophysical aspects whicht differs from that observed in local communities in semi-arid environments in Brazil, where local classifications of the forests correspond purely with utilitarian characteristics (Da Silva et al 2016) but agrees with the multidimensionality observed in neighboring areas among multicultural groups (Stampella 2018;Zamudio and Hilgert 2016). In the same way, the different landscape vegetation units perceived in our region were similar to those recorded by Pirondo and Keller (2015) in a community of guaranitic descent in the wetlands of northeast Corrientes province, where the denomination of the environments was assigned according to the abundance of certain vegetal species.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Likewise, when analyzing the way these landscape units are named, a complex series of factors is involved. Most of the names assigned describe biophysical aspects whicht differs from that observed in local communities in semi-arid environments in Brazil, where local classifications of the forests correspond purely with utilitarian characteristics (Da Silva et al 2016) but agrees with the multidimensionality observed in neighboring areas among multicultural groups (Stampella 2018;Zamudio and Hilgert 2016). In the same way, the different landscape vegetation units perceived in our region were similar to those recorded by Pirondo and Keller (2015) in a community of guaranitic descent in the wetlands of northeast Corrientes province, where the denomination of the environments was assigned according to the abundance of certain vegetal species.…”
Section: Discussionmentioning
confidence: 90%
“…In general terms, to evaluate a forest status of conservation, floristic surveys are carried out where the structure of communities (richness, abundance and vital status of species, (mainly woody ones) is measured. However, historical evidence suggests that, despite their harmonious and functional appearance, it is unlikely that untouched environments exist to date (Stampella 2018). In this sense, it is proposed that species of cultural importance, potentially managed in situ, are included when surveying the structure of communities in order to analyze emerging information that the effect of past and current use and management could be reflecting (Araújo and Ferraz 2014;Levis et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This disuse is based in the current use of the trifoliata (hardy or trifoliate orange) as a rootstock, changing local cooking and medicinal practices, and in the decrease in the production and 2: A, D, E) was also traditionally practiced before 1950; locals gathered scion wood of these varieties as well as others found in the monte (the forest, or areas of spontaneous vegetation) to graft. Other reticulata) have a relatively recent history in the area; however, they have been culturally appropriated, resignified (i.e., with new local denominations), and widely represented in the local knowledge (for further details, see Stampella et al 2013aStampella et al , 2014.…”
Section: Citrusmentioning
confidence: 99%